2023
DOI: 10.1038/s42003-023-04708-2
|View full text |Cite
|
Sign up to set email alerts
|

Collateral activity of the CRISPR/RfxCas13d system in human cells

Abstract: CRISPR/Cas13 systems are increasingly used for programmable targeting of RNAs. While Cas13 nucleases are capable of degrading both target RNAs and bystander RNAs in vitro and in bacteria, initial studies fail to detect collateral degradation of non-target RNAs in eukaryotic cells. Here we show that RfxCas13d, also known as CasRx, a widely used Cas13 system, can cause collateral transcriptome destruction when targeting abundant reporter RNA and endogenous RNAs, resulting in proliferation defect in target cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 27 publications
3
33
1
Order By: Relevance
“…Knowing this, we evaluated the targeting capabilities of the Hi-Fi RfxCas13d variants, RfxCas13d-N1V7, -N2V7 and -N2V8, as well as DiCas7-11, in HEK293T cells transiently transfected with the mATXN2-T2A-EGFP-encoding reporter plasmid alongside an mCherry-encoding reporter, whose fluorescence was used as a proxy for collateral targeting. Consistent with prior studies demonstrating that targeting highly expressed reporter transcripts in mammalian cells can lead to robust collateral effects [50][51][52][53][54] , we found that, when programmed to target mATXN2-T2A-EGFP, the native RfxCas13d protein reduced mCherry fluorescence by ~40-60% (P < 0.001; Fig. 6a and Supplementary Fig.…”
Section: High-fidelity Cas13 and Cas7-11 Can Target Ataxin-2supporting
confidence: 91%
See 4 more Smart Citations
“…Knowing this, we evaluated the targeting capabilities of the Hi-Fi RfxCas13d variants, RfxCas13d-N1V7, -N2V7 and -N2V8, as well as DiCas7-11, in HEK293T cells transiently transfected with the mATXN2-T2A-EGFP-encoding reporter plasmid alongside an mCherry-encoding reporter, whose fluorescence was used as a proxy for collateral targeting. Consistent with prior studies demonstrating that targeting highly expressed reporter transcripts in mammalian cells can lead to robust collateral effects [50][51][52][53][54] , we found that, when programmed to target mATXN2-T2A-EGFP, the native RfxCas13d protein reduced mCherry fluorescence by ~40-60% (P < 0.001; Fig. 6a and Supplementary Fig.…”
Section: High-fidelity Cas13 and Cas7-11 Can Target Ataxin-2supporting
confidence: 91%
“…We next evaluated if RfxCas13d could knock down the endogenous mATXN2 transcript and if its targeting induced collateral effects in cells, as RfxCas13d-mediated trans-cleavage can lead to the degradation of non-specific RNA [50][51][52][53][54] . To answer this first question, we transfected Neuro2A mouse neuroblastoma cells with RfxCas13d and crRNA-10, the most efficient mATXN2-targeting crRNA identified from our initial screen.…”
Section: Targeting Ataxin-2 With Rfxcas13dmentioning
confidence: 99%
See 3 more Smart Citations